Simplify and solve the following linear equation:
15(y-4) - 2(y-9) + 5(y+6) =0
15(y-4) -2(y-9)+5(y+6) = 0
Opening the brackets, we have
 15y -60 - 2y + 18 + 5y + 30 =0
Collecting the like terms,
Â
(15-2+5)y + (-60 + 18 +30) =0
or                   18y + (-12) =0
Transposing (-12) to RHS, we have
                               18y = 12
or                                 (Dividing both sides by 18)
∴                                   Â
Simplify and solve the following linear equation:
3(5z - 7) - 2(9z - 11) = 4(8z - 13) - 17